Quelle remédiation à l'anxiété de performance en classe ? Une étude comparant trois conditions d’évaluation en vue de minimiser l’anxiété mathématique - Hanin, Vanessa; Lepareur, Céline; Hascoët, Marine; Pouille, Jérémy; Gay, Philippe (La Revue LEeE, 2022)
The aim of this study is to determine if certain forms of remediation during a test situation can limit the level of performance anxiety in mathematics. For this purpose, 115 secondary school students in the canton of Vaud answered several questionnaires asking them to imagine themselves in three different scenarios: (1) taking a summative test without the possibility of remediation; (2) taking a summative test with the possibility of doing a remediation test in case of failure with conservation of the best of the two scores and; (3) taking a summative test with the possibility of remediation, but only the last of the two scores is taken into account. Comparisons of these three conditions using repeated measures ANOVAs indicate that students report as much anxiety on a test without remediation as on a test with remediation where only the last score is kept. In contrast, students report significantly less anxiety when only the best performance is considered. Moreover, gender had a significant influence on the parameters of anxiety, so that the difference between the conditions seemed to be more marked for girls than for boys. These results lead us to consider that the principle of "right to error", in essence the possibility of keeping the best of the two scores, is potentially an effective remediation system to limit the negative effects of performance anxiety in mathematics. Pedagogical implications are discussed in the interpretation of the results.
Keywords: remédiation